The ancient synagogue from its origins to 200 C.E. : a source book - Runesson, Anders. (Ancient Judaism and Early Christianity, 2008)
Despite the recent explosion of research on ancient synagogues, investigators in the field have hitherto been forced to cull relevant evidence from a vast assortment of scholarly publications. This volume gathers for the first time all of the primary source material on the early synagogues up through the Second Century C. E. In the case of literary, epigraphic and papyrological evidence, catalog entries contain the texts in their original language and in English translation. For archaeological remains, entries provide technical descriptions along with plans and photographs. All listings are accompanied by bibliographic citations and interpretative comments. An Introduction frames the current state of synagogue research, while extensive indices and cross-references allow for easy location of specific allusions. An appendix to the catalog contains source materials on Jewish temples outside of Jerusalem.